Asymmetry in the Qy Fluorescence and Absorption Spectra of Chlorophyll a Pertaining to Exciton Dynamics - Reimers, Jeffrey R.; Rätsep, Margus; Freiberg, Arvi (Frontiers in Chemistry, 2020)
Significant asymmetry found between the high-resolution Qy emission and absorption spectra of chlorophyll-a is explained, providing basic information needed to understand photosynthetic exciton transport and photochemical reactions. The Qy spectral asymmetry in chlorophyll has previously been masked by interference in absorption from the nearby Qx transition, but this effect has recently been removed using extensive quantum spectral simulations or else by analytical inversion of absorption and magnetic circular dichroism data, allowing high-resolution absorption information to be accurately determined from fluorescence-excitation spectra. To compliment this, here, we measure and thoroughly analyze the high-resolution differential fluorescence line narrowing spectra of chlorophyll-a in trimethylamine and in 1-propanol. The results show that vibrational frequencies often change little between absorption and emission, yet large changes in line intensities are found, this effect being also strongly solvent dependent. Among other effects, the analysis in terms of four basic patterns of Duschinsky-rotation matrix elements, obtained using CAM-B3LYP calculations, predicts that a chlorophyll-a molecule excited into a specific vibrational level, may, without phase loss or energy relaxation, reemit the light over a spectral bandwidth exceeding 1000 cm-1 (0.13 eV) to influence exciton-transport dynamics.